The COVID-19 Health Protocol among University Students: Case Studies in Three Cities in Indonesia - Daniel, D.; Kurniawan, Arif; Indah Pinawati, Ajeng Rahastri; Thohira, Morrin Choirunnisa; Annaduzzaman, Md. (MDPI, 2022)
The COVID-19 pandemic has caused lifestyle changes for everyone and led to the practice of regulated health protocols for preventing the spreading or severity of the COVID-19 pandemic. This study examines the differences in health protocols and health practices among university students. The designed online survey was conducted among 292 university students in three cities in Indonesia, i.e., Yogyakarta, Semarang, and Surakarta. A forced-entry multivariate regression was conducted using all RANAS (risk, attitude, norms, ability-self-regulation) sub-factors as independent variables and health protocol obtained from PCA as the dependent variable. The results showed that the students’ health protocol and health practices were practiced with varying frequency. A face mask covering the chin and nose was the most practiced health protocol, while reducing mobilization by maintaining distance was the most violated health protocol among students. We also found that four health protocol practices are highly correlated, i.e., handwashing in public spaces, physical distancing, frequency of using the mask, and avoiding crowded places. In addition, three significant psychological factors were identified, which were positively associated with the student’s health protocol practice, i.e., belief about time (attitude) (OR: 0.119; CI: −0.054–0.136; p ≤ 0.05), personal norm (norm) (OR: 0.232; CI: 0.149–0.539; p ≤ 0.01), and action control (self-regulation) (OR: 0.173; CI: 0.046–0.427; p ≤ 0.05), where the personal norm is the most significant one. Finally, to minimize the COVID-19 transmission among students, especially when they back to onsite learning, it was important to create students’ sense of ethical self-obligation to follow and practice standard health hygiene correctly and regularly.